Participatory model building for suicide prevention in Canada - Thompson, Laura H; Lang, Justin J; Olibris, Brieanne; Gauthier-Beaupré, Amélie; Cook, Heather; Gillies, Dakota; Orpana, Heather (Université d'Ottawa | University of Ottawa, 2020)
Abstract Background Suicide is a behaviour that results from a complex interplay of factors, including biological, psychological, social, cultural, and environmental factors, among others. A participatory model building workshop was conducted with fifteen employees working in suicide prevention at a federal public health organization to develop a conceptual model illustrating the interconnections between such factors. Through this process, knowledge emerged from participants and consensus building occurred, leading to the development of a conceptual model that is useful to organize and communicate the complex interrelationships between factors related to suicide. Methods A model building script was developed for the facilitators to lead the participants through a series of group and individual activities that were designed to elicit participants’ implicit models of risk and protective factors for suicide in Canada. Participants were divided into three groups and tasked with drawing the relationships between factors associated with suicide over a simplified suicide process model. Participants were also tasked with listing prevention levers that are in use in Canada and/or described in the scientific literature. Results Through the workshop, risk and prevention factors and prevention levers were listed and a conceptual model was drafted. Several “lessons learned” which could improve future workshops were generated through reflection on the process. Conclusions This workshop yielded a helpful conceptual model contextualising upstream factors that can be used to better understand suicide prevention efforts in Canada.